The Use of Smart Box Media in Teaching Synonyms and Antonyms to Improve Students’ Vocabulary at SMA Kristen 1 Kupang - Timo, Putri A.; Marpaung, Tiarma; Tlonaen, Zuvyati (English Education Study Program - Artha Wacana Christian University, 2024)
This study aimed to enhance vocabulary mastery in teaching synonyms and antonyms using smart box media among eleventh-grade students at SMA Kristen 1 Kupang. Employing a classroom experimental design, researchers conducted pre-tests, applied treatment using smart box media, and followed up with post-tests to evaluate outcomes. Quantitative analysis of the scores revealed significant improvement, substantiating the efficacy of the intervention. Initially, students in the experimental class scored a cumulative 790 in the pre-test. After implementing smart box media, their total post-test score increased to 1300, marking a 64% improvement. The calculation used for these scores involved dividing the number of correct responses by the total number of questions, multiplying by 100, and summing all individual scores. The overall percentage increase was derived using a formula where the difference between the final and initial results was divided by the initial score and multiplied by 100. These results indicate that smart box media is a powerful tool for enhancing vocabulary acquisition. The significant score increases highlights that integrating innovative teaching aids can substantially boost student engagement and learning effectiveness. Thus, the study concludes that the use of smart box media in teaching vocabulary, particularly synonyms and antonyms, is highly effective and beneficial for eleventh-grade students at SMA Kristen 1 Kupang, offering a promising approach for vocabulary instruction in similar educational contexts.